Perancangan Kafe, Ruang Kerja, dan Ruang Serbaguna Dengan Pendekatan Indoor Health and Comfort oleh Filostudio - Santoso, Agatha Luis; Susan, Susan (Universitas Ciputra Surabaya, 2024)
Late 2019 saw the emergence of the COVID-19 virus in China, and early 2020 saw its global spread. A room with good ventilation helps prevent the spread of the COVID-19 virus. This research uses quantitative methods by collecting data through surveys on Google Forms. The client's desire to be realized in this building design is the concept of smart, aesthetic, and green buildings. The client's needs that want to be realized in building design when using the services of an interior architecture consultant include requiring a building that has comfort and safety for users, a building with a healthy environment, and a building that maximizes the use of natural lighting and ventilation. Designing cafes, workspaces, and multi-purpose rooms with an approach to indoor health and comfort aims to create an environment that supports its users' health, comfort, and productivity. This approach can help answer the COVID-19 issue by creating rooms with good ventilation to prevent the spread of COVID-19. An approach to indoor health and comfort is a design that considers visual comfort, thermal comfort, noise control, healthy material selection, monitoring CO2 levels in the building, the introduction of outside air, and a smoke-free building. With this design, it is hoped that it can become an example of a building with this approach to indoor health and comfort so that many buildings will apply this approach to produce healthy and comfortable buildings for users.